Factors affecting performance excellence in Indonesian state-owned enterprises - Muhammad Iqbal; Yudi Azis; Sucherly; Umi Kaltum (Problems and Perspectives in Management)
State-owned enterprises (SOEs) have a strategic position as architects of public services, balancing large private powers, helping to foster small businesses or cooperatives, and a considerable basis of state revenue in numerous forms of taxes and dividends. For Indonesia to compete in the global market, its economic actors (private sector, SOEs, and cooperatives) must amplify their performance. This paper aims to explore the factors affecting performance excellence in Indonesian SOEs, namely business environment and innovation capability through business strategy. Data were obtained from questionnaires distributed to 100 directors/managers representing SOEs in 12 clusters. The partial least squares structural equation modeling (PLS-SEM) procedures were operated to evaluate the path coefficients and identify the pivotal factors of each construct using SmartPLS. The results exhibited that the business environment (β = 0.357, p < 0.05) and innovation capability (β = 0.518, p < 0.05) positively and significantly affected Indonesian SOEs’ business strategy. Meanwhile, business environment (β = 0.263, p < 0.05), innovation capability (β = 0.273, p < 0.05), and business strategy (β = 0.459, p < 0.05) positively and significantly affected SOEs performance excellence. Moreover, business strategies can partially mediate the effect of the business environment (β = 0.164, p < 0.05) and innovation capability (β = 0.238, p < 0.05) on performance excellence. An important implication of this study is that to maintain and improve performance excellence, SOEs must first focus on the capability of innovation to initiate the implementation of business strategies by constantly addressing the business environment.